The cardiovascular safety of tricyclic antidepressants in overdose and in clinical use - David Taylor; Sofia Poulou; Ivana Clark (SAGE Publishing, 2024)
Tricyclic antidepressants (TCAs) remain widely prescribed for depression and many other conditions. There may be important differences between individual TCA in regard to their overdose toxicity and their cardiac toxicity in clinical use. We conducted a systematic review to compare the toxicity of individual TCA in overdose and the risk of serious adverse cardiac events occurring with therapeutic doses. We used the fatal toxicity index (FTI) and case fatality ratio as markers of fatality in overdose, and hazard ratios or odds ratios for the risk of cardiovascular adverse events during normal clinical use. In all, 30 reports of mortality in overdose and 14 observational studies assessing the risk of cardiovascular adverse events in clinical use were included. FTI values were of the same order of magnitude (10 1 -10 2 ) for all TCAs except lofepramine. Desipramine appears to be somewhat more likely than other TCAs to lead to death in overdose. Amitriptyline, clomipramine, dothiepin/dosulepin, doxepin, trimipramine and imipramine showed broadly similar toxicity and were usually reported to be less toxic than desipramine. Data on nortriptyline were contradictory. Lofepramine had the lowest risk of death in overdose. The rank order of overdose toxicity was broadly consistent between different FTI definitions and between markers used. With respect to the risk of cardiovascular events at clinically relevant exposure, amitriptyline, nortriptyline and lofepramine were associated with a greater risk of in-use cardiotoxicity. All measures of overdose toxicity were subject to external influences and confounding. The continued use of TCAs in depression and other conditions should be minimized when considering their undoubted toxicity in overdose and possible toxicity in normal clinical use.